Workshop on WA-PPG Application (Wolfram Alpha, Photo Math, Padlet, Geogebra) to Support the Pedagogical and Professional Competence of Mathematics MGMP Teachers in 50 Regency Cities in Implementing the Independent Curriculum - Suherman, Suherman; Al Aziz, Saddam; Martha, Zamahsary; Fitria, Dina (Fakultas MIPA Universitas Negeri Padang, 2024)
The independent curriculum requires teachers to have professional competence in understanding the material and pedagogical competence in designing teaching modules according to the material. Teachers experience many obstacles. Teachers can overcome these obstacles by utilizing technological developments in learning (TPACK). The solution was provided by a Wolfram Alpha, Photo Math, Padlet, Geogebra, or WA-PPG application workshop for High School Mathematics MGMP teachers, Harau District, 50 City Regency. Based on pre-test and post-test data from 31 teachers, an N-Gain score for professional competence and 0.55 was obtained for pedagogy. This means that workshops are genuinely able to improve teacher competence. Apart from that, the average questionnaire score for the practicality of using the WA-PPG application was 80.24%, which concluded that the WA-PPG application used by teachers during the workshop was practical and easy to use.